The Argumentation Functional’s Of Repetition In Arabic Rhetorical - Ramdani, Farida (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : Repetition is undertaken a lot of argumentation function’s; in Arabic rhetoric, and every function therein is determined by semantic relation’s contained in the context however, the most often in the repetition is the persuasive function’s that takes different forms and dimentions depending on the type of discourse, after continuous search; we found that prophetic rhetoric is the richest corpus that we can search in it about argumentation repetition’s component, that’s what this paper is looking for. .